2023
DOI: 10.1002/dmrr.3681
|View full text |Cite
|
Sign up to set email alerts
|

Lower skeletal muscle mass is associated with diabetes and insulin resistance: A cross‐sectional study

Abstract: AimsThe association between skeletal muscle mass and diabetes incidence/insulin resistance/glycated hemoglobin (HbA1C) is unknown. The aim of this study was to investigate such association in clinically apparently healthy males and females.MethodsA cross‐sectional study of 372,399 Korean males and females who completed bioelectrical impedance analysis (BIA) in a health‐screening programme was performed. Skeletal muscle index was used as an indicator of skeletal muscle mass. Skeletal muscle index (%) [appendicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Usually, greater muscle mass is associated with greater insulin sensitivity. Park et al[ 5 ] reported that lower skeletal muscle mass is associated with greater insulin resistance. However, previous studies have shown that a greater muscle mass index is associated with greater insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, greater muscle mass is associated with greater insulin sensitivity. Park et al[ 5 ] reported that lower skeletal muscle mass is associated with greater insulin resistance. However, previous studies have shown that a greater muscle mass index is associated with greater insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Accompanying islet α- and β-cell dysregulation in T2D at the microscopic scale, alterations in body composition may take part in the processes of T2D at the macroscopic scale. Body composition alterations in T2D patients are characterized by increases in whole-body fat mass, ectopic fat deposition (visceral fat accumulation), and a decrease in skeletal muscle mass [ 5 , 6 ]. Is there any relationship between the macroscale of body composition and the microscale of α- and β-cell dysfunctions in the background of T2D?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In individuals with obesity, it proves sufficiently reliable for estimating fat mass, exhibiting a strong correlation and minimal bias compared to DXA [ 27 ]. Two cross-sectional studies, involving over 400,000 Korean adults, employed BIA as a dependable option for measuring skeletal muscle, further affirming its reliability in the diverse populations [ 28 , 29 ]. In this study, VSR was computed as an indicator of MASLD risk by dividing the VFA (cm 2 ) by SMM (kg).…”
Section: Methodsmentioning
confidence: 99%
“… 3 Previous studies have shown that it is associated with increased secretion of inflammatory cytokines and insulin resistance. 5 Therefore, reduced skeletal muscle mass disturbs normal glucose metabolism and affects insulin sensitivity and blood sugar levels. Sarcopenia is considered to be a novel complication observed in the middle-aged and elderly population with T2DM and has received increasing attention in recent years.…”
Section: Introductionmentioning
confidence: 99%